Factors Affecting Online Purchasing Of Local Food - Avivah Rahmaningtyas; Slamet Hartono; Any Suryantini (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2017)
The purpose of this research are to analyze which factors can influence Indonesia’s consumer intention to buy local food by online and whether the intention can affect to purchasing decision or not. This research used Partial Least Square (PLS) as data analysis with significance level 5%. There are several requirements to fulfil the criteria of data anlaysis, they are convergent validity, discriminant validity, and composite reliability. The result is all of three requirement is achieved. Bootstrapping analysis was used to examine the significance and verify the hypotheses. There were five independent variables and two dependent variables. The independent variables were perceived usefulness, perceived ease of use, perceived trust, perceived risk, and perceived price. The dependent variables were intention to buy and purchasing decision. There are two variables which are significance towards intention to buy, they are perceived risk and perceived price. Perceived risk is significance and consistent with the theory which has negative effect towards intention to buy, while perceived price is significance and has positive effect towards intention to buy. Perceived usefulness, perceived ease of use, and perceived trust are not significant toward intention to buy. Variables intention to buy is intervention variable which affect significantly towards purchasing decision. R-square score for intention to buy is 30.5% while r-square score for purchasing decision is 25.9%.